2022
DOI: 10.3390/ejihpe12020014
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Can Improve Consumers’ Hygienic Food-Handling Behavior to Reduce the Transmission Risk of Antimicrobial-Resistant Bacteria through Food

Abstract: antimicrobial-resistant (AMR) bacteria spread via food to humans and can seriously impair infection treatment. Hygienic food handling is an effective measure to avoid the transmission of bacteria. Therefore, we tested three types of interventions (tailored, generic, and no intervention) for their effectiveness in improving consumers’ hygienic food handling against the spread of antimicrobial-resistant bacteria through foods in a longitudinal randomized control trial. We based the determinants of hygienic food-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
1
1
Order By: Relevance
“…In other words, the significant effectiveness of the intervention will be more apparent over time. However, this is not in consistent with Freivogel, Lehmann, and Visschers's study (2022). One possible reason is that the length of time from intervention to postsurvey is not the same.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In other words, the significant effectiveness of the intervention will be more apparent over time. However, this is not in consistent with Freivogel, Lehmann, and Visschers's study (2022). One possible reason is that the length of time from intervention to postsurvey is not the same.…”
Section: Discussioncontrasting
confidence: 82%
“…Existing research has not come to a conclusion yet on the relationship between short‐ and long‐term effects of interventions. Interventions are likely to produce immediate results, but the effect is likely to decrease with longer follow‐up periods (Freivogel et al, 2022; Redmond & Griffith, 2006). Some studies have not reported an obvious change in behaviors during the postsurvey follow‐up (e.g., Beavers et al, 2015; Diplock et al, 2018), whereas other have found that long‐term training stimulates positive and permanent changes (Sanli̇er et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%